RESULTS OF THE TARGETED SELECTIVE AND BREEDING WORK OF THE SIMMENTAL RED-AND-MOTLEY BREED OF DAIRY CATTLE - A. E. Chindaliyev, A. E.; Baimukanov, D. A.; Karynbayev, A. K.; Chindaliyev, E. (Scientific Journal of Pedagogy and Economics, 2018)
The article presents the characteristics of selective-breeding work with the "Ertis" red-and-motley cattle of the Simmental breed created by scientists of the KazSRIAB&FP LLP, on the basis of improving the Simmental breed of cattle in the direction of raising dairy productivity using the gene pool of imported servicing bulls. The aim was to summarize the results of targeted selective and breeding work for the period after approbation of animals of the new "Ertis" red-and-motley dairy type of cattle of the Simmental breed by the example of the herd of Kirov LLP, as well as the current state of their productivity. The average indices of productivity of the main selection traits were taken into account, such as milk yield for 305 days of lactation, fat and protein percentage, live weight, and also their average duration of productive use. Where the percentage of fat and protein was determined by modern devices on the analyzers of the integrated milk quality system (Milkoscan FT+, Fossomatic FT+) and statistical data were processed according to standard methods. As a result, for the period 2009 - 2016, a significant increase in the productivity of cows was achieved, the average milk yield for 305 days in lactation in the herd was increased by 2089 kg or 54.4% (from 3829±42.3 to 5928±27.8). According to the last completed lactation, the average milk yield per cow for 305 days by the first lactation was 5040.1±65.16 kg of milk (n=108), by the second - 5814.1±49.66 kg (n=385), by the third and older lactation 6269.7±37.76 kg (n=410). The average duration of productive use of cows was 2.8 lactations (lim 1-9), of which the third and older lactations were 45.4%. Thus, the targeted selective and breeding work to improve the productive qualities of the "Ertis" red-and-motley type of cattle of the Simmental breed in the Kirova LLP is quite profitable and acceptable for further breeding and its selection preservation